신노년세대의 시니어 주거에 대한 선호조사와 미래 방향 고찰 - 권순정; 박화옥; 임정원; 윤극한 (의료·복지 건축, 2023)
Purpose: This study is to analyze the preferences for future senior housing that reflects the characteristics of the new generation of seniors and to consider the direction of future senior housing. Methods: Data from an online survey of a new generation of older adults and group interviews with professionals and baby boomers were analyzed. The data collected from the survey and interview have been using quantitative analysed method. Literature surveys also have been carried out. Results: The results show that future senior housing requires a change in perception through conceptual expansion from the Aging in Place (AIP) to the Aging in Community (AIC) paradigm. The preferences of the new generation of seniors for future senior housing were examined to determine their preferences for location, facility size and type, unit floor plans and services, and living costs. Implications: The direction of senior housing services and architectual plans for seniors aged 55 to 65 years old were discussed.
Keywords: 노후주거; 베이비부머; 신노년세대; 은퇴 후 주거선호; senior housing; baby boomers; new generation of seniors; post-retirement housing preferences